Measuring patient safety culture using the hospital survey on patient safety culture pasca pandemic Covid-19 - Pipin Sumantrie; Martalina Limbong; Sondang Sidabutar (Science Midwifery, 2023)
The patient safety system is a top priority that must be implemented by the hospital, this is very closely related to both the image of the hospital and patient safety. The current Covid-19 pandemic situation requires serious attention from the health service, in order to avoid transmission of respiratory diseases and other nosocomial infections, so that patient safety is a priority. The aim of this research is to determine the implementation of patient safety management carried out at Adventist Hospital. This study used a quantitative descriptive design, using a survey questionnaire from the Hospital Survey on the Hospital Survey of Patient Safety Culture (HSOPSC) from Healthcare Research and Quality (AHRQ). Which was carried out from November to December 2021, using the Cluster Random Sampling technique. This study gave positive results on aspects of the dimensions of hospital management support for patient safety in patient safety culture question items such as Hospital management actions showing that patient safety is a top priority, with a percentage of 81.7%, the lowest positive aspect is the patient safety aspect. dimensions of training and organizational learning on the question item: in contact with our colleagues, we improve our safety practices, with 0.8 % of respondents. Patient safety is currently an aspect that is of concern to almost every service provider, especially hospitals, with more and more hospital management conducting patient safety measurement processes using the HSOPSC survey, the patient safety aspect will increase.